Enhanced organic photovoltaic-based retinal prosthesis using a cathode-modified structure with plasmonic silver nanoparticles: a computational study - Rahmani, Ali; Eom, Kyungsik (Frontiers in Cellular Neuroscience, 2024)
Organic interfaces have recently emerged as a breakthrough trend in biomedical applications, demonstrating exceptional performance in stimulating retinal neuronal cells owing to their high flexibility and compatibility with tissues. However, the primary challenge associated with organic photovoltaics is their low efficiency compared to that of their inorganic counterparts. Among different approaches, embedding plasmonic metal nanoparticles (NPs) in active or buffer layers can efficiently improve photovoltaic cell performance. Methods: A cathode decorated with silver nanoparticles is introduced to increase the absorption phenomena and improve the interface performance as a computational study. In addition to embedding spherical silver nanoparticles in the active layer (A-AgNPs), a monolayer array of spherical AgNPs in the cathode electrode (K-AgNPs) is incorporated. In this configuration, the large K-AgNPs play dual roles: acting as cathode electrode and serving as plasmonic centers to increase light trapping and absorption. The bulk heterojunction PCPDTBT:PCBM is chosen as the active layer due to its favorable electronic properties. Results: Our computational analysis demonstrates a notable 10% enhancement in the photovoltaic cell current density for the developed structure with K-AgNPs in contrast to without them. Additionally, the simulation results reveal that the modeled device achieves a two-fold efficiency of the bare photovoltaic cell (without A-AgNPs and K-AgNPs), which is particularly evident at a low intensity of 0.26 mW/mm². Discussion: This study aims to propose an efficient epiretinal prosthesis structure using a different strategy for plasmonic effects rather than conventional methods, such as incorporating NPs into the active or buffer layer. This structure can prevent the harmful side effects of using large metal NPs (r>10 nm) in the active layer during exciton quenching, charge trapping, and recombination, which deteriorate the power conversion efficiency (PCE).